HOW STRONG WAS IMPACT-INDUCED CO2 DEGASSING IN THE CRETACEOUS-TERTIARY EVENT? NUMERICAL MODELING OF SHOCK RECOVERY EXPERIMENTS - Ivanov B.A.; Langenhorst F.; Deutsch A.; Hornemann U. (My University, 2002)
The impact-induced release of CO2 is one of the potentially most important mechanisms to explain drastic and rapid changes of the climate at the Cretaceous-Tertiary (K-T) boundary. General predictions, modeling, and laboratory experiments, however, yield questionable estimates on the amplitude of CO2 outgassing. We present new results on shock recovery experiments with calcite. A new approach is used to better understand experimental results: the numerical simulation of the shock loading and following release of the samples. The calculations allow us to construct detailed pressure-temperature paths for different parts of a sample. Mineralogical observations, as well as modeling, indicate that at low and moderate pressures (<~70 GPa in the reverberation experiments), compact calcite develops deformation effects, such as dislocations and mechanical twins, whereas the major effect for release from high shock pressures is melting, not degassing. In porous or preheated calcite, shock and postshock temperatures are higher, resulting in a lowering of the threshold for melting and degassing. The presence of specific textures, e.g., bubbles and foamy aggregates, indicative of a mobilized gaseous phase in porous samples, in combination with the absence of CaO, is interpreted as the result of a rapid back reaction due to the high affinity of CO2 to lime. To delimit kinetic effects seems to be of fundamental importance for a proper estimate of the CO2 release from carbonate lithologies in the context of the Chicxulub impact event.
Keywords: Cretaceous; Mesozoic::Cretaceous; Мезозой::Меловая